An Assessment of the Distribution of Public-Sector Educational Investment in Pakistan: 1970-71 - 1982-83 (Review Article, Note, Comment) (The Pakistan Development Review, 1986)
Planning documents for the Seventies emphasized the importance of primary education and the curtailment of the mushrooming growth at the higher level. Our review suggests that this policy has had only partial success in implementation. Viewed in the context of educational planning theory and the evidence available for Pakistan, the policy is found to be sound. While the benefits of a correct distribution of investment within the educational sector are self-evident, resource constraints have been leading to an overall underinvestment in the educational sector. We show that Pakistan's public sector education is highly subsidized and so to supplement the limited resources devoted to it, we recommend, as a possible solution, a selective application of user charges.